Advanced Free-Space Optical Communication Techniques and Applications III 2017
DOI: 10.1117/12.2292004
|View full text |Cite
|
Sign up to set email alerts
|

15 Gb/s OFDM-based VLC using direct modulation of 450 GaN laser diode

Abstract: A record data rate for visible light communications (VLC) using a transistor outline (TO) packaged Gallium Nitride (GaN) laser diode is reported. Using a system 3 dB bandwidth of 1.4 GHz data transmission at 15 Gb/s is reported. This is achieved due to the use of orthogonal frequency division multiplexing (OFDM) in combination with a high system signal to noise ratio (SNR) and adaptive bit loading extending the effective bandwidth to 2.5 GHz. To the best of authors knowledge this is the highest reported data r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…Moreover, it has been shown that LED-based communication (which has been standardised by IEEE as 802.15.7) [33,96] offers higher data rates. According to some researchers, theoretical data rates for LED-based lighting communication is more than 15 Gbps [30]. While this inherent data communication capability is available on the downlink because of the readily available lighting infrastructure and user devices, equipped with photoreceivers and cameras, capable of detecting light.…”
Section: Discussion and Open Research Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, it has been shown that LED-based communication (which has been standardised by IEEE as 802.15.7) [33,96] offers higher data rates. According to some researchers, theoretical data rates for LED-based lighting communication is more than 15 Gbps [30]. While this inherent data communication capability is available on the downlink because of the readily available lighting infrastructure and user devices, equipped with photoreceivers and cameras, capable of detecting light.…”
Section: Discussion and Open Research Challengesmentioning
confidence: 99%
“…Different research groups have demonstrated that a single gallium nitride (GaN)-based LED can achieve a data rate of up to 4 Gb/s [ 28 , 29 ]. A high data rate of up to 15 Gb/s and 13.5 G b/s using a GaN blue laser diode was achieved for a distance of 15 cm and 197 cm, respectively [ 30 ].…”
Section: Visible Light Communication Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Although flat fading has been widely adopted to model OWC channels [52], the channel might become frequencyselective when the nonlinearity of optoelectronic devices is considered [52], [54]- [57]. Optoelectronic devices have a particular range where the frequency response can be considered flat.…”
Section: Amplitude-coherent Detection For Optical Ofdmmentioning
confidence: 99%
“…The flat range where the frequency response is flat mostly depends on the device characteristics and driving current. Some high quality devices such as the OSRAMs PL450B [54] can provide a near-flat bandwidth of about 1 GHz. In the case that higher transmission bandwidth is desired, or the design aims at using low-cost devices that do not have large flat range, then pre-distortion and pre-leveling techniques can be used to linearize the spectrum [58]- [61].…”
Section: Amplitude-coherent Detection For Optical Ofdmmentioning
confidence: 99%